Danse moriendi. O muzyczno-tanatologicznych aspektach późnej twórczości lirycznej Jarosława Marka Rymkiewicza - Dembińska-Pawelec, Joanna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The sketch shows relations of the late poetry of Jarosław Marek Rymkiewicz with a music and the topic of death. Poet articulates a belief that transverbal property of music deepens and extends the ability of poetry to express the thanatological matters. Rymkiewicz describes life as a constant tending to death. This tending is shown in his poems as a danse moriendi, dance in a rhythm of waltz or ländler. Through the music it connects with the cosmic rhythm of nature, the wheel of every existence. Rymkiewicz convinces also that lyrical poetry related with music can defy nothingness. Thanks to oniristic poetic creation poems-songs and poems-ariettes preserve, as in a fairy tale, the continuity of life.